Factors affecting repurchase intentions in retail shopping: An empirical study. Issue 9 (September 2022) - Chatzoglou, Prodromos; Chatzoudes, Dimitrios; Savvidou, Athina; Fotiadis, Thomas; Delias, Pavlos
Abstract: The present study investigates the factors affecting consumer repurchase intentions in retail stores. More specifically, it emphasizes on the concept of in-store customer shopping experience. In that direction, a new conceptual framework (research model) is developed and empirically tested, using primary data collected from retail store customers. The proposed model includes twelve research factors that are classified into three dimensions (groups): six independent factors (antecedents), five mediating factors and repurchase intention (dependent factor). In more detail, the study examines the antecedents of customer behavior, which constitute the in-store customer shopping experience (Physical environment, Interior shop environment & layout, Interaction with the staff, Interaction with other customers, Merchandise value/quality, Merchandise variety). It argues that the effect of the antecedents on repurchase intention is indirect, mediated through five other factors (mediators) (Customer experience, In-shop emotions, Perceived value, Customer satisfaction, Customer loyalty). Under that context, eleven research hypotheses were tested, using the Structural Equation Modeling (SEM) technique. The final sample includes 618 retail store customers, who participated in a web-survey. Results offer support for the underling mechanism of the proposed research model, arguing that antecedents significantly affect the mediators, which, in turn, affect the repurchase intention of retail shoppers. Results indicate that in order to have more return customers, retailers should enhance their interior shop environment and layout and increase the value of their merchandise. The originality of the study lies in its three-dimensional approach. It offers an understanding about the mechanism that impacts repurchase intentions, an approach lacking in the relevant literature. Moreover, it focuses on all kinds of retail stores, offering wider generalizability of its empirical findings. Also, it examines in-store emotions and experience of customers inside a store, two factors which very seldomly have been investigated in the context of physical retail stores. Abstract : Retail stores, Shopping experience, Customer experience, Customer satisfaction, Customer loyalty, Repurchase intention.